1994
DOI: 10.1111/j.1365-2885.1994.tb00276.x
|View full text |Cite
|
Sign up to set email alerts
|

Stereospecific pharmacodynamics and pharmacokinetics of carprofen in the dog

Abstract: The non-steroidal anti-inflammatory drug (NSAID) carprofen (CPF) contains a single chiral centre. It was administered orally to Beagle dogs as a racemate (rac-CPF) at a dose of 4 mg per kg body weight and as individual (-)(R) and (+)(S) enantiomers at 2 mg per kg body weight. Each of the enantiomers achieved similar plasma bioavailability following administration as the racemate as they did following their separate administration. Only the administered enantiomers were detectable when the drug was given in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
98
3
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(112 citation statements)
references
References 16 publications
10
98
3
1
Order By: Relevance
“…36 It has high plasma concentration in cats, achieving levels from 25 to 50 mg/L after administration of a low dose of 4 mg/kg during the first 7 h. 37 However, in dogs, the plasma levels were inferior (between 2 and 15 mg/L) for the same dose. 38 In humans, the plasma levels after a single oral dose of 150 mg rose to 10 mg/L during the first 5 h after administration. 39 The half lethal dose (LD 50 ) of carprofen in mice is 282 mg/kg and in rats it is 149 mg/kg.…”
Section: Discussionmentioning
confidence: 99%
“…36 It has high plasma concentration in cats, achieving levels from 25 to 50 mg/L after administration of a low dose of 4 mg/kg during the first 7 h. 37 However, in dogs, the plasma levels were inferior (between 2 and 15 mg/L) for the same dose. 38 In humans, the plasma levels after a single oral dose of 150 mg rose to 10 mg/L during the first 5 h after administration. 39 The half lethal dose (LD 50 ) of carprofen in mice is 282 mg/kg and in rats it is 149 mg/kg.…”
Section: Discussionmentioning
confidence: 99%
“…Our results correspond with their study, as we also did not find any change of this parameter in pigs after administration of carprofen or meloxicam. Unlike McKellar, we were not able to monitor values of thromboxane B2 as an indicator of COX activity of platelets (McKellar et al 1990(McKellar et al , 1994. We also did not detect significant APTT and PT deviations in control animals after administration of carprofen or meloxicam.…”
Section: Discussionmentioning
confidence: 82%
“…Buccal mucosal bleeding time and clotting ability (McKellar et al 1990) were not affected by administration of carprofen. McKellar et al (1990McKellar et al ( , 1994 monitored thromboxane B2 as an indicator of COX activity of platelets and found that in vitro administration of carprofen did not impair the platelets' production of thromboxane B2.…”
mentioning
confidence: 99%
“…Karprofen derişiminin 1-10 g / ml arasında olmasının ise, kıkırdak matriks bütünlüğünün korunmasında ve kıkırdak proteoglikan yıkımına herhangi bir dolaysız etkisi olmadan, seçici bir şekilde, yeni kıkırdak GAG sentezini uyararak potansiyel yararlı bir etki sağladığı görülmüştür. 24,37 . …”
Section: Tablo 4 Tetrasiklinlerin Etkileri 15unclassified